Antiprotozoal activity of flavonoids from Eupatorium arnottianum - Clavin, Maria Liliana (2017)
Dichloromethane and ethanol extracts of Eupatorium arnottianum were evaluated for invitroleishmanicidal activity. The dichloromethane extract produced 80% and 85% of growthinhibition on both Leishmania mexicana and Leishmania amazonensis promastigotes respectively,at a concentration of 100 μg/mL. At the same concentration, the ethanol extract inhibited thegrowth of L. mexicana and L. amazonensis promastigotes in 62% and 65% respectively. Bioassayguidedfractionation of these extracts led to the isolation and identification of flavonoids nepetin,eupatilin, jaceosidin, eriodictyol and hyperoside as bioactive compounds against both species ofLeishmania with IC50 values <10 μg/mL, with nepetin being the most active compound againstboth Leishmania species (IC50 values <2 μg/mL). On Trypanosoma cruzi epimastigotes, jaceosidin,eupatilin and nepetin were found to be the most active flavonoids, with IC50 values 0.06, 0.89 and2.94 μg/mL respectively. It was observed by transmission electron microscopy that eupatilin andjaceosidin induced intense cytoplasmic vacuolization on L. mexicana promastigotes, followedby parasite destruction. Nepetin induced a mild vacuolization, although the morphology ofparasites was preserved. On T. cruzi epimastigotes, eupatilin and jaceosidin induced a moderatevacuolization and some kinetoplast swelling while nepetin did not induce any significant effectson parasites. At the ultrastructural level, the differential effects of eupatilin and jaceosidin onboth trypanosomatids may indicate that these molecules affect selectively certain targets onLeishmania spp. We conclude that plants from the Eupatorium genus could be an importantsource of compounds (flavonoids) with leishmanicidal and trypanocidal activity, thus constitutingan interesting option for the treatment of parasitic diseases.